Secondary-level Teachers’ Perceptions and Challenges of Using ICT in Mathematics Classroom - Ghimire, Deepak (Karnali Outlook: Knowledge Across Disciplines, 2026)
This article investigates secondary-level mathematics teachers’ perceptions of ICT use and the barriers preventing effective classroom integration in Surkhet district, Nepal, focusing on Chingad Rural Municipality and Birendranagar Municipality. The study employed a mixed-methods research design, using survey questionnaires and semi-structured interviews for data collection. The population consisted of all secondary mathematics teachers in the selected municipalities, from which 20 teachers were purposively selected as key informants. Data were analyzed thematically. The findings reveal that teachers generally hold positive perceptions of ICT and recognize its potential to enhance student motivation, engagement, and discovery-based learning in mathematics. Most teachers expressed a strong willingness to use ICT to support reading, writing, and problem-solving activities. However, actual classroom integration of ICT was limited and inconsistent. Major barriers included inadequate technical knowledge and skills, low confidence, and a lack of ICT-focused training, particularly in rural schools. Although many schools had ICT resources, these were mainly confined to computer laboratories or libraries and were rarely used in regular mathematics classrooms. The study concludes that the availability of ICT infrastructure alone is insufficient for effective integration. Meaningful use of ICT in mathematics education requires adequate teacher training, direct access to technology in classrooms, and ongoing technical support. Addressing these challenges is essential for achieving sustainable and pedagogically effective ICT integration in secondary-level mathematics teaching and learning in Nepal.